Bolus thrombolytic infusion during prolonged refractory cardiac arrest of undiagnosed cause. Issue 3 (23rd February 2006) - Sheth, A; Cullinan, P; Vachharajani, V; Conrad, S A
Abstract : Acute myocardial infarction (AMI) and pulmonary embolism (PE) account for about 70% of cardiac arrest. Although thrombolytic therapy is an effective therapy for both AMI and PE, it is not routinely recommended during cardiopulmonary resuscitation (CPR) for fear of life threatening bleeding complications. Numerous case reports and retrospective studies have suggested a beneficial effect of thrombolytics in cardiac arrest secondary to AMI and PE; however, we present a case of successful use of bolus thrombolytics during CPR in a patient with undifferentiated cardiac arrest (undiagnosed cause) after prolonged conventional resuscitation without success.